Dangerous Ideas: The Force of Ideology and Personality in Driving Radicalization. Issue 1 (2nd January 2019) - Hertog, Steffen
ABSTRACT: Graeme Wood's The Way of the Strangers gets as close as is humanly possible to an ethnography of recruiters and sympathizers of the Islamic State. Contrary to much writing on radical Islamism, Wood convincingly shows that the Islamic State's ideas—rooted in a literalist reading of ancient Islamic sources—are central in motivating many of the movement's followers. His accounts of individual adherents also suggests, however, that ideas are not the only factor, as certain personality traits influence who is attracted to radical Islamist movements.